Autoregressive Integrated Moving Average (ARIMA) Simulation Methods In Product Inventory 9969B Printable Splicing Tape - Utomo, Yitno; Prihono; Muhamad Abdul Jumali; Febrin Auliau Rohman (UNIPA PRESS, 2024)
Simulation is applied to the 9969B Printable Splicing Tape product. The ARIMA (Autoregressive Integrated Moving Average) method, which is a method that is based on the values ​​of changes that have occurred in the past, is then used to determine historical data patterns. The aim of this research is to simulate forecasting inventory control needs for Printable Splicing Tape stock. The temporary ARIMA model is p = 8 (PACF dying down plot), d = 2 (one differencing), and q = 1. So, the temporary ARIMA model obtained is (8, 2, 1). The sales forecast for all Printable Splicing Tape products type 9969B on average per month during June-December 2023 is estimated that the average forecast for the company's Inventory Control must stock 608 rolls with a tracking error of -1 (e < 4) so ​​it is very permissible, because it is less than quaternion.